1999
DOI: 10.1159/000024220
|View full text |Cite
|
Sign up to set email alerts
|

Fragrance and Contact Allergens in vitro Modulate the HLA–DR and E–Cadherin Expression on Human Epidermal Langerhans Cells

Abstract: Background: Epidermal Langerhans cells (LCs) play a critical role in the induction of contact hypersensitivity. The LCs leave the skin, move to the regional lymph nodes and present the allergens embedded in the HLA–DR molecule to naive T–lymphocytes. To allow LC emigration from the epidermis, E–cadherin must be downregulated. In this study, we have examined the early events that occur in the human epidermis after exposure to three strong contact sensitizers and two commonly used fragrances by examining alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 19 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…UV irradiation to skin lipid has been shown to generate acrolein [Niyati-Shirkhodaee and Shibamoto, 1992] and to cause a number of pathologic skin conditions such as in¯amma-tion, cancer development, and aging [Robinson et al, 1989;Dypbukt et al, 1993;Grafstrom et al, 1994;Coverly et al, 1998;Verrier et al, 1999]. Till present we do not have any data that exactly measured the concentration of acrolein in the UV-irradiated local skin tissue.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…UV irradiation to skin lipid has been shown to generate acrolein [Niyati-Shirkhodaee and Shibamoto, 1992] and to cause a number of pathologic skin conditions such as in¯amma-tion, cancer development, and aging [Robinson et al, 1989;Dypbukt et al, 1993;Grafstrom et al, 1994;Coverly et al, 1998;Verrier et al, 1999]. Till present we do not have any data that exactly measured the concentration of acrolein in the UV-irradiated local skin tissue.…”
Section: Discussionmentioning
confidence: 66%
“…Skin is another target of environmental acrolein, and is the site of endogenous production of acrolein from lipid following ultraviolet (UV) irradiation [Niyati-Shirkhodaee and Shibamoto, 1992]. In skin, acrolein may cause non-immunological contact hypersensitivity [Coverly et al, 1998;Verrier et al, 1999] and can display cytotoxicity and genotoxicity [Robinson et al, 1989;Dypbukt et al, 1993;Grafstrom et al, 1994]. Acrolein is known to act as a potent inhibitor of DNA excision repair enzymes, and this is believed to underlie the acrolein-mediated cytopathic effects [Robinson et al, 1989;Dypbukt et al, 1993;Grafstrom et al, 1994].…”
mentioning
confidence: 99%
“…According to the review by Ryan et al (2005), changes in Langerhans cells as a result of exposure to chemical allergens include internalization of surface major histocompatibility complex (MHC) class II molecules via endocytosis (Becker et al, 1992;Girolomoni et al, 1990), induction of tyrosine phosphorylation (Kühn et al, 1998), modulation of cell-surface markers (Aiba and Katz, 1990;Verrier et al, 1999) and changes of cytokine expression (Enk and Katz, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…SDS did not significantly affect expression of these antigens [38]. Also, Degwert et al [39] showed that short incubation (up to 3 hrs) of MoDCs with subtoxic concentrations of sensitizers (e.g., NiSO 4 ), but not with irritants (SLS, benzalkonium chloride), down-regulated HLA-DR expression.…”
Section: Discussionmentioning
confidence: 97%